After-tourism revisited - Philippe Bourdeau (Via@)
The “imperfect and provisional” after-tourism interpretative framework was proposed to give an account of tourism’s changing status, practices and representations. It was presented as a composite notion, intended to link together three mutant modalities of modern tourism, namely post-tourism(s), trans-tourism and hyper-tourism.This paper applies a reflexive approach to the genesis, developmental stages, reception and evolutions of this proposal. It resituates the after-tourism perspective as being anchored in research directions that have been focused on the recomposition of relations between the here and the elsewhere and on the heuristic contribution of “critical” situations and practices. This approach has been nurtured by the author’s engagement in collectives positioned at different geographical and temporal levels. Moreover, it has emerged from a constant iteration between on the one hand normative and non-normative registers and on the other geographical, thematic, scientific and pedagogical anchors.